PENGEMBANGAN E-BOOK PADA MATA KULIAH SOSIOLOGI PENDIDIKAN PROGRAM STUDI TEKNOLOGI PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI MAKASSAR - Syarifa Ratu Lutfiah Quraish Ihsan Ba’sein; Nurhikmah H; Farida Febriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
In the Sociology of Education Course, the problems that occur for students require a combination of learning resources into one such as an E-Book. So the researchers developed the E-Book for Educational Sociology Courses. This study aims to: 1) describe the level of need for the E-Book, 2) describe the design of the development of the E-Book, 3) describe the level of validity and practicality of the E-Book. This research used the R&D approach and was developed using the ADDIE model. Data collection used a needs identification questionnaire, a content/material expert validation questionnaire, a design and media expert questionnaire, a group trial questionnaire, an individual trial questionnaire, and a questionnaire for the responses of the lecturers of the Education Sociology Course. The results of the research show that the identification of the level of student needs is at a percentage of 87.05% of the required qualifications. Furthermore, the validation results from content/material experts were at a percentage of 92.8%, very valid qualifications, the validation of design experts was at a percentage of 96.66%, very valid qualifications, in group trials, the percentage results were 98.33%, very practical qualifications. individual trials are in the percentage of 100% very practical qualifications and the responses of the lecturers who teach the course are in the percentage of 100% very practical qualifications. The conclusion of the research results is that the level of needs analysis for the Sociology of Education E-Book is in the required qualifications and this E-Book is very valid and very practical.